Simulated volume loss in the base of tongue in a virtual swallowing model. Issue 4 (4th July 2019) - Wang, Jing; Ho, Andrew Kenneth; Papadopoulos-Nydam, Georgina; Rieger, Jana; Inamoto, Yoko; Fels, Sidney; Saitoh, Eiichi; Guo, Chuanbin; Aalto, Daniel
Abstract: Dysphagia often occurs in patients with oropharyngeal cancer, particularly in those with base of tongue lesions after surgery both with and without chemoradiation therapy. Tongue volume loss is related to functional impairment in swallowing; however, the physiological mechanisms related to the impairment are still unclear. This study aimed to clarify possible causal links between volume loss and swallowing outcomes by simulating volume loss in a 3D computer fluid model of swallowing. An artificial volume loss was introduced to a reference swallowing model of a healthy subject. Swallowing assessments that are commonly used in clinical practice were used to evaluate the simulations. The simulation of impairment showed an increase in oral and pharyngeal residue. Tongue volume loss appeared to be the mechanism which caused increased pharyngeal residue in the virtual simulations. Major limitations of the simulations were oversimplified models and volume loss as a single parameter with no consideration of biophysical compensations. Discussion of limitations suggested that with improved simulation techniques, mechanisms of dysphagia could be better understood. In conclusion, this study indicated that volume loss of the base of tongue may contribute to increased oropharyngeal residue.